The moderating effect of corporate governance on conditional conservatism and earnings management - Chan, Bi Xuan (2022)
Analytical literature presents ambiguous views on how conditional conservatism impacts earnings management. Despite being widely cited that conservatism limits accruals-based earnings management, this assumption is not well supported by empirical evidence. Also, no other study on this topic has been conducted in countries other than the US. Thus, with a UK sample of 1129 firm-year observations obtained from 2010-2018, this study tests the effects of conservatism on accruals-based and real earnings management, employing the Ordinary Least Square (OLS) approach. Results confirm that conservatism reduces accrual manipulation but simultaneously triggers a substitution of accrual management with real earnings management.